Synchrony Financial - Sonnenfeld, Jeffrey A., 1954-; Elias, Jaan; Rosenthal, Jean, active 2017 (London : Yale School of Management, 2017)
When Synchrony Financial came into existence in 2014, the company was part start-up, part established financial giant. For 80 years, Synchrony's businesses had been part of General Electric, until GE spun off the entity. It fell to Margaret Keane, Synchrony's first CEO, to integrate the best of the company's legacy with new practices. Especially, she looked for new practices that would help Synchrony attract millennials, whose employment expectations, credit needs, and retail preferences appeared to differ from the previous generations.
Originally published in Sonnenfeld, J. A., Elias, J., & Rosenthal, J. (2017). Synchrony Financial. 17-012. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/synchrony-financial.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Keane, Margaret, -- active 2014.; Synchrony Financial; General Electric Company; Generation Y -- Employment